Analysis of Metaphors Applied in Mobile Legends Game - Irta Fitriana; Misbakhul Munir Rois (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2023)
The purpose of this study is to analyze metaphors applied in the Mobile Legends game. It is a research on semantics approach since the focus of the study is investigating the meaning as seen from characters’ utterances. Metaphor is a kind of figurative language that is learned in semantics. Figurative language is seen as a creative way of using language to express a more-in-depth meaning via a creative style more than literally. The use of metaphors occurs in online games, like Mobile Legends, to strengthen the gamer’s emotions and feelings. This research applied (Perrine and Arp, 1992) theory to investigate metaphors used in Mobile Legends through the characters' utterances. This study employed qualitative and descriptive research. The data for this research are the utterances of all the characters in the Mobile Legend game. After analyzed, the results show that there are 31 utterances using metaphor. It is aimed to personalize the character’s role more real and to give imaginative influences to the listener or player. The metaphors used are able to stir the player’s emotions through the metaphorical language shown in the utterances.